Metal Chelates of Ambidentate Ligand Cysteine and Antiulcer Drug Ranitidine - Mathur, Mala; Srivastava, Savita; Srivastava, N.M. (Asian Journal of Chemistry, 2010)
The role of metal complexes in biological systems is of paramount importance. Mixed ligand complexes, wherein one ligand is a drug and another such an amino acid which makes part of the living system, can affect the activity of drug to a remarkable degree. Antiulcer drug is selected for the present study as it has potent donor atoms/groups in its structure while amino acids act as ambidentate ligand useful in formation of chelate rings involving various coordination sites. Mixed ligand complexes of ranitidine, an antiulcer drug and cysteine, an amino acid, with Mn(II), Co(II), Cu(II) and Zn(II) have been synthesised and characterised.